TINJAUAN YURIDIS KEDUDUKAN KEPALA OTORITA IKN DALAM SISTEM PEMERINTAHAN DI INDONESIA: Legal Review of the Position of the Chief of the IKN Authority within Indonesia's Governance System - Farhan, Mohammad Rahul; Syam, Radian (Faculty of Law, Universitas Trisakti, 2024)
This study discusses the direct appointment of the Nusantara Capital Region Authority Chief by the President, bypassing general elections, raising questions about consistency with the underlying democraticprinciples of the Indonesian State. Although the 1945 Constitution grants the public the right to elect local leaders through general elections, the direct appointment of the Nusantara Capital Region Authority Chief creates tension with these principles, prompting inquiries about leadership legitimacy and the role between central and regional governance. Employing normative legal research methods and descriptive-analytical analysis of secondary data from literature, this study highlights the inconsistency between the appointment of regional heads and the fundamental democratic principles of the state. The implications of this appointment raise concerns regarding accountability, public representation, and alignment with democratic principles. The findings underscore the importance of maintaining consistency in the application of legal regulations in regional head elections, particularly in the Nusantara Capital, as a robust foundation for a transparent, accountable, and people-respecting democratic process.